Comparative prognostic value of parameters of right ventricular pulsatile afterload in patients with advanced heart failure awaiting heart transplantation. (3rd October 2022) - Rubino, F; Scarsini, R; Piccoli, A; San Biagio, L; Tropea, I; Pighi, M; Prati, D; Tavella, D; Onorati, F; Faggian, G; Ribichini, F
Abstract: Background: Right ventricular (RV) function demonstrated a strong impact on survival of patients with advanced heart failure with reduced ejection fraction (HFrEF). In particular, increased RV pulsatile afterload (RVPA) was associated with poor prognosis. Several right heart catheterization-derived parameters have been proposed to characterize RVPA, including pulmonary artery compliance (PAC), elastance (PAE) and pulsatile index (PAPi). However, among these indices, the best prognostic indicator is undetermined. Purpose: To assess the prognostic relevance of RVPA parameters in patients with advanced HFrEF evaluated for heart transplantation. Methods: 149 patients with end-stage HFrEF underwent right heart catheterization during the evaluation for heart transplantation. All patients were clinically followed up until death or any censoring events including heart transplantation, left ventricular assist device (LVAD) and hospitalization for acute heart failure. Cox regression and ROC-curve analysis were used to test the prognostic value of RVPA determinants. Multivariate regression models with C-statistics were used to test the independent predictive value of RVPA indices. Results: The mean age of the study population was 56.6±10.1 years and 85.2% were male. The most frequent aetiology of HFrEF was ischemic cardiomyopathy (52.3%). Mean LV ejection fraction was 25.7±10.2%. During a mean follow up time of 17±15 months, 29 (19.5%) patients met the primary endpoint: 9 (6%) patients died, 4 (2.68%) patients underwent an urgent heart transplantation, 11 (7.3%) patients underwent urgent LVAD implantation (as bridge to transplantation therapy) and 5 (3.3%) were hospitalized for HF. Patients who met the primary endpoint were significantly older patients (61.2±7.8 vs 55.4±10.2, p=0.006) and with worse hemodynamic profile than event-free survivors (PAC [1.8±0.8 vs. 2.7±2.0, p=0.01], mPAP [33.5±11.3 vs. 29.3±11.0, p=0.05], PVR [3.0±1.6 vs. 2.6±2.0, p=0.09] and PAE [1.12±0.5 vs. 0.98±0.6, p=0.04]). Among the RVPA parameters PAC<1.9 mL/mmHg (HR 4.0, CI 1.3–6.0, p=0.007) and PAE>0.9 mmHg/mL (HR 2.5, 95% CI 1.1–5.2, p=0.02) were associated with the primary endpoint. On the contrary, PAPi was not significantly associated with the outcome. PAC demonstrated a superior predictive value for the composite adverse outcome compared with pulmonary vascular resistances (PVR) (AUC comparison p=0.019) and PAPi (p=0.03) but similar compared with PAE (p=0.19) and mPAP (p=0.51). In multivariable regression models, PAC, but not PAE showed incremental prognostic value compared with cardiac index (p=0.02). Conclusions: Hemodynamic indices of RVPA are associated with worse survival in patients with end-stage heart failure. In particular, PAC and PAE demonstrated superior prognostic value compared with PAPi and steady-state PVR. Moreover, PAC showed incremental prognostic value compared with cardiac index in patients awaiting heart transplantation. Funding Acknowledgement: Type of funding sources: None.